2021
DOI: 10.3390/brainsci12010013
|View full text |Cite
|
Sign up to set email alerts
|

The PACAP/PAC1 Receptor System and Feeding

Abstract: Pituitary adenylyl cyclase activating polypeptide (PACAP) belongs to the vasoactive intestinal polypeptide (VIP)/secretin/glucagon superfamily. PACAP is present in two forms (PACAP-38 and PACAP-27) and binds to three guanine-regulatory (G) protein-coupled receptors (PAC1, VPAC1, and VPAC2). PACAP is expressed in the central and peripheral nervous systems, with high PACAP levels found in the hypothalamus, a brain region involved in feeding and energy homeostasis. PAC1 receptors are high-affinity and PACAP-selec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…We have previously reported that asprosin failed to directly regulate some neuron types including POMC-expressing neurons, serotonin neurons, dopamine neurons, steroidogenic factor-1 neurons, and neuron populations in the paraventricular hypothalamic nucleus neurons ( 2 ), which are relevant for feeding and glucose homeostasis. However, some other neuron types—including the cannabinoid receptor 1–expressing neurons ( 53 ), pituitary adenylate cyclase–activating polypeptide–releasing neurons ( 54 ), neuronal nitric oxide synthase–expressing neurons ( 55 , 56 ), and brain-derived neurotrophic factor–releasing neurons ( 57 )—in the ventral medial of hypothalamus (VMH) have been identified for the regulation of food intake, glucose homeostasis, and energy expenditure. It is possible that apsrosin also acts on those VMH neuron populations to further regulate feeding behavior and glucose homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that asprosin failed to directly regulate some neuron types including POMC-expressing neurons, serotonin neurons, dopamine neurons, steroidogenic factor-1 neurons, and neuron populations in the paraventricular hypothalamic nucleus neurons ( 2 ), which are relevant for feeding and glucose homeostasis. However, some other neuron types—including the cannabinoid receptor 1–expressing neurons ( 53 ), pituitary adenylate cyclase–activating polypeptide–releasing neurons ( 54 ), neuronal nitric oxide synthase–expressing neurons ( 55 , 56 ), and brain-derived neurotrophic factor–releasing neurons ( 57 )—in the ventral medial of hypothalamus (VMH) have been identified for the regulation of food intake, glucose homeostasis, and energy expenditure. It is possible that apsrosin also acts on those VMH neuron populations to further regulate feeding behavior and glucose homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…PACAP is a 38-amino-acid or 27-amino-acid neuropeptide produced and released both in the periphery and the CNS, especially in the VMN, or in the LHA and PVN in the hypothalamus [ 148–150 ]. PACAP binds to three GPCRs: PAC1R, VPAC1, and VPAC2 [ 151 ]. Its metabolic pathways are linked to the regulation of body weight and the development of obesity and metabolic syndrome.…”
Section: Anorexigenic Neuropeptidesmentioning
confidence: 99%
“…Together, these findings raise the intriguing possibility that PACAP and PAC1R signaling may have critical roles in β -cell function. Moreover, β -cell production and release of proteolytically mature PACAP-38 in response to glucose may represent a mechanism to ensure its own insulin release but also to communicate the feeding state to PAC1 receptors in the hypothalamus and other brain regions that control feeding behavior ( Sekar et al, 2017 ; Sureshkumar et al, 2021 ). It is worth noting that there was a discrepancy in the mRNA and protein expression, with ADCYAP1 mRNA specifically enriched in β cells, whereas PACAP protein was detected in δ cells via immunohistochemistry ( Elgamal et al, 2023 ; Yang et al, 2023 ).…”
Section: The Human Islet G Protein–coupled Receptor Transcriptomementioning
confidence: 99%